Choosing Between Trimmed L-moment and L-moment Estimators of Extreme Value Distribution (Type- I) - AL-kanani, Iden; Sameer, Fadhaa (Iraqi Journal of Science, 2023)
Trimmed Linear moments (TL-moments) are natural generalization of L-moments that do not require the mean of the underlying distribution to exist. It is known that the sample TL-moments is unbiased estimators to corresponding population TL-moment. Since different choices for the amount of trimming give different values of the estimators it is important to choose the estimator that has minimum mean squares error than others. Therefore, we derive an optimal choice for the amount of trimming from known distributions based on the minimum errors between the estimators. Moreover, we study simulation-based approach to choose an optimal amount of trimming and maximum like hood method by computing the estimators and mean squares error for range of trimming and choose the one which has minimum mean squares error .